Commerce application with multiple accessible methods / Yang Mei Lin - Yang , Mei Lin (2003)
The E-Commerce M-Commerce (ECMC) is a B2C application which provides different accesibility for reading materials'marketing within Malaysia by using e-commerce and m-commerce applications. This system can be accessed through Internet, PDA or hand phone. It is divided into both user and administrator module with appropriate access control for different types of users. The e-commerce and m-commerce's history, categories, scope, WAP Technology, client/server architectures and reading material's publishers have been discussed. Furthermore, the analysis of systems has been carried out to identify the strength and weaknesses of each system to develop a better system. The methodology chosen for the project is waterfall model. Besides, the chosen development tools and system requirements are analyzed. The program design, database design, interface design is elaborated to make development process easier and more efficient. Meanwhile, the four phases involved in the implementation stage are database implementation, module implementation, interface implementation and security implementation. The testing strategies involved are unit testing integrated testing and system testing. The top-down approach is adopted for integration testing. In system testing, functional testing, performance testing, acceptance testing and end user evaluation were carried out. System evaluation discusses the problem encountered during the development stage and solutions, strength, limitation, future enhancement of the system. Moreover, knowledge and experience gained are also elaborated in this topic. In short, ECMC project increases the convenience and efficiency of user without being restricted by time and locations as well as minimizes the time needed to perform a transaction.